Risk factors associated with zoonotic diseases derived from pig production: A scoping review - Pulido-Villamarín, Adriana (2022)
Colombian pork production has increased over the years; however, given the socioeconomic conditions of the country, people who are related to these farms can acquire zoonotic pathogens and develop disease. To identify the risk factors associated with the transmission of zoonotic diseases, a review of the literature was carried out following the steps of a «scoping review»; by searching for scientific articles in the MEDLINE, Web of Science and SciELO databases, applying DeCS terms. In total, 31 documents met the inclusion criteria and were analyzed. For the transmission of zoonotic diseases from pig farming to humans, the risk factors described were: poor higiene habits of workers, inadequate handling of animal and human excreta, and the presence of pests on farms such as rodents, among others; however, the information related to this type of pathology is scarce, so it is necessary to continue with the development of additional studies that allow identifying new risk factors and deepen the existing ones to prevent their presentation.